(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article is devoted to dangerous infectious diseases and their modern methods of treatment. It discusses the threat of infectious diseases to human health, their main characteristics and serious complications. The article also explains modern methods of treatment, such as antiviral and antibiotic drugs, vaccination, monoclonal antibodies, genetic and molecular therapy, telemedicine and digital monitoring. The article shows scientific achievements in the prevention and effective treatment of dangerous infectious diseases, emphasizing their importance for human health.